Competetiveness of the Montenegrin fruit and vegetables sector and recommendtations for impovement - Jovovic, Radislav (Applied Studies in Agribusiness and Commerce, 2012)
A number of facts, primarily including high fragmentation at all levels, weak vertical integration, limited dimensions in comparison to competitors poor technological level and unbalanced quality/price ratio make the sector weak, low competitive and exposed to international competition, reducing its capacity to capture any existing market potential. Almost all opportunities are frozen by prevailing weaknesses and threat impacts are exacerbated by a largely prevailing number of weaknesses. High production unit cost appears to be a major constraint to local supply market competitiveness. This situation appears to be mainly caused by general low levels of productivity – provoked by not adequate and up-to-date cultivation practices, reduced levels of input use, utilisation of old and, therefore, less performing varieties, and also farm management shortcomings. High losses from reduced availability of post-harvest facilities and equipment add up to the problem. The improvement of the sector is not easy. In other words, there is a lot to do for the Montenegrin sector operators to increase sales: tackle imports and increase market shares in the domestic market and abroad. Based on our research, we suggest that the Montenegrin fruit and vegetable sector should primarily aim at substituting imports, increasing domestic consumption and developing exports to the region (CEFTA countries) primarily via promising market opportunities. Based on our analyses of the state of affairs of the sector, the competitiveness and the market potentials, the recommendations for improvement competitiveness are outlined.